2016
DOI: 10.1038/gt.2016.60
|View full text |Cite
|
Sign up to set email alerts
|

Cationic microRNA-delivering nanocarriers for efficient treatment of colon carcinoma in xenograft model

Abstract: Manipulation of tumor microRNAs (miRNAs) may offer novel avenues for treatment of cancer. However, development of safe, robust, non-viral delivery methods remains a main challenge to obtain the promise of gene therapy. The miR-145 is dysregulated in many cancers, including colon carcer, and further in vitro investigation established antiproliferative and proapoptotic roles of miR-145. Herein, we study a PLGA/PEI (poly (d, l-lactide-co-glycolide)/polyethylenimine)-mediated miRNA vector delivery system; the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 43 publications
1
39
0
1
Order By: Relevance
“…31 Exosome samples were lysed in sodium dodecyl sulfate loading buffer. After boiling, equal amounts (10 μg) of the proteins were electrophoresed on 12% sodium dodecyl sulfate-polyacrylamide gels and transferred to Immobilon ® membranes (Millipore, Bedford, MA, USA) using wet blotting methods, and then transferred onto polyvinylidene fluoride membrane, and blocked and incubated with monoclonal antibodies APO (1:500), CD63 (1:1,000), CD9 (1:1,000), GAPDH (1:1,000), CCND2 (1:1,000), CCNE2 (1:500), CDK6 (1:500), and β-actin (1:1,000) overnight, respectively.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…31 Exosome samples were lysed in sodium dodecyl sulfate loading buffer. After boiling, equal amounts (10 μg) of the proteins were electrophoresed on 12% sodium dodecyl sulfate-polyacrylamide gels and transferred to Immobilon ® membranes (Millipore, Bedford, MA, USA) using wet blotting methods, and then transferred onto polyvinylidene fluoride membrane, and blocked and incubated with monoclonal antibodies APO (1:500), CD63 (1:1,000), CD9 (1:1,000), GAPDH (1:1,000), CCND2 (1:1,000), CCNE2 (1:500), CDK6 (1:500), and β-actin (1:1,000) overnight, respectively.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…30 Moreover, our group developed a poly(lactic-coglycolic acid)/polyetherimide/hyaluronan (PLGA/PEI/HA)-based vehicle as a carrier of miR-145 and further showed that PLGA/PEI/HA/miRNA complexes were delivered efficiently to tumor cells within colon carcinoma xenografts in mice where they exhibited significant antitumor effects. 31 Inspired by the findings of these earlier studies, we have developed a new approach to repurpose exosomes as living vehicles that can deliver nucleic acid therapeutics to target cells. In particular, Apo-A1, the main component of highdensity lipoprotein (HDL), was expressed as a fusion with the transmembrane protein CD63 to facilitate its presentation on the surface of the exosome.…”
mentioning
confidence: 99%
“…This therapeutic approach has been tried in colon and hepatocellular carcinomas and hepatic metastasis (that may arise from primary CRC) and, in cell culture and in mice orthotopic models, recovers the expression of downregulated tumor suppressor miRNAs miR-26a, miR-33a, miR-34a, or miR-145. Overexpression of these miRNAs with mimics resulted in inhibition of cancer cell proliferation and apoptosis, or in tumor reduction, prolonged survival, and disease protection in animals [356, 372374]. In 2013, the first miRNA mimic entered phase 1 trial in patients with primary liver cancer or metastatic cancer with liver involvement under the name of MRX34, a double-stranded RNA delivered by Smarticles (licensed liposomes which comprise different mixtures of palmitoyl oleoyl phosphatidyl choline, dioleoyloxytrimethylammoniumpropane, 1,2-dimyristoylglycerol-3-hemisuccinate, and cholesterol) (http://www.mirnatherapeutics.com/) [113].…”
Section: Colorectal Cancer Treatments and Biomarkersmentioning
confidence: 99%
“…These liposomes can even be coated with carbohydrates, peptides, or antibodies to direct them towards cell types that express specific receptors or antigens. Similarly, siRNAs or miRNAs can be incorporated in polymer-based nanoparticles (10–100 nm), as those containing polyethyleneimine that have been reported to be efficient for the therapy of CRC in cell culture and mouse xenografts by restoring miR-33a or miR-145 function [373, 374]. Antibody-based methods have been also described.…”
Section: Colorectal Cancer Treatments and Biomarkersmentioning
confidence: 99%
“…Thus modification of PEI might improve the physicochemical properties of PEI. A study of reducible PEI was reported by synthesis of high molecular weight PEI (25,000 Da) with cetyl bromide, and then conjugated with PLGA polymer and cross-linked with HA to facilitate the cellular uptake of tumor-suppressor miR-145 (Liang et al, 2016). …”
Section: Vector Systems To Deliver Mirnasmentioning
confidence: 99%